A global synthesis of high-resolution stable isotope data from benthic foraminifera of the last deglaciation - Muglia, Juan; Mulitza, Stefan; Repschläger, Janne; Schmittner, Andreas; Lembke-Jene, Lester; Lisiecki, Lorraine; Mix, Alan; Saraswat, Rajeev; Sikes, Elizabeth; Waelbroeck, Claire; Gottschalk, Julia; Lippold, Jörg; et al. (Scientific data, 2023)
We present the first version of the Ocean Circulation and Carbon Cycling (OC3) working group database, of oxygen and carbon stable isotope ratios from benthic foraminifera in deep ocean sediment cores from the Last Glacial Maximum (LGM, 23-19 ky) to the Holocene (<10 ky) with a particular focus on the early last deglaciation (19-15 ky BP). It includes 287 globally distributed coring sites, with metadata, isotopic and chronostratigraphic information, and age models. A quality check was performed for all data and age models, and sites with at least millennial resolution were preferred. Deep water mass structure as well as differences between the early deglaciation and LGM are captured by the data, even though its coverage is still sparse in many regions. We find high correlations among time series calculated with different age models at sites that allow such analysis. The database provides a useful dynamical approach to map physical and biogeochemical changes of the ocean throughout the last deglaciation.